2019
DOI: 10.1080/02699052.2019.1574328
|View full text |Cite
|
Sign up to set email alerts
|

Opioids and cerebral physiology in the acute management of traumatic brain injury: a systematic review

Abstract: Background: Following traumatic brain injury (TBI), optimization of cerebral physiology is recommended to promote more favourable patient outcomes. Accompanying pain and agitation are commonly treated with sedative and analgesic agents, such as opioids. However, the impact of opioids on certain aspects of cerebral physiology is not well established. Objective: To conduct a systematic review of the evidence on the effect of opioids on cerebral physiology in TBI during acute care. Methods: A comprehensive litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…In contrast, individuals with mild TBI (ie, concussions) had 10% higher odds of using opioids. Little is known about the long-term consequences of opioid treatment in persons with TBI, 28 however, opioids may increase the risk of cognitive and mental problems in persons with TBI. 29 More studies on the long-term effect of opioids on TBI outcomes, as well as the factors that influence the initiation and continuation of opioid use among persons with TBI, 18 are required.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, individuals with mild TBI (ie, concussions) had 10% higher odds of using opioids. Little is known about the long-term consequences of opioid treatment in persons with TBI, 28 however, opioids may increase the risk of cognitive and mental problems in persons with TBI. 29 More studies on the long-term effect of opioids on TBI outcomes, as well as the factors that influence the initiation and continuation of opioid use among persons with TBI, 18 are required.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids and benzodiazepines reduce cerebral metabolic oxygen consumption with minimal effects on cerebral perfusion, which makes them ideal agents for the management of TBI. [810] However, exposure to opioids for the acute management of TBI may increase risk for dependence and opioid use disorder in these patients. We and others have shown that in-hospital exposure to opioids increases the risk for chronic opioid use in surgical patients [1113]; with persistent use reported as much as one year after the index admission.…”
Section: Introductionmentioning
confidence: 99%
“…Different opioids may be used like fentanyl, sufentanil, remifentanil, and morphine. Opioids are beneficial for analgesia, but their bolus administration may increase ICP with associated decreases in MAP and CPP, and should be avoided (29). In the systematic review Wiener and coworkers have found no consistent results between different opioids, and between opioid and non-opioid analgesia in the management of traumatic brain injury regarding their effects on MAP, ICP, or CPP (29).…”
Section: Acute Brain Injury and Pain Controlmentioning
confidence: 99%
“…Opioids are beneficial for analgesia, but their bolus administration may increase ICP with associated decreases in MAP and CPP, and should be avoided (29). In the systematic review Wiener and coworkers have found no consistent results between different opioids, and between opioid and non-opioid analgesia in the management of traumatic brain injury regarding their effects on MAP, ICP, or CPP (29). Opioid consumption can be reduced by the use of dexmedetomidine for sedation without affecting neurological function (30).…”
Section: Acute Brain Injury and Pain Controlmentioning
confidence: 99%